Caracterización agro socio productiva y ambiental de la parroquia Belisario Quevedo del cantón Latacunga, provincia de Cotopaxi, 2022. - Giler Andache, Mauricio Daniel (2022)
This project was developed in the rural parish of Belisario Quevedo, belonging to the canton of Latacunga, Province of Cotopaxi, located in Latacunga. Lack of knowledge regarding the agro-socio-productive conditions of the parish, the role played by the state,and the private sector has been inefficient since there is no evidence of improvements in the dynamics of life and production of the inhabitants of the parish. Therefore, the mainobjective of this research is to characterize the agro-socio productive situation of the Belisario Quevedo parish in the canton of Latacunga, Province of Cotopaxi. The Participatory Rural Appraisal (PRA) methodology was applied to achieve the present purpose, establishing economic, social, and environmental indicators in the form of asurvey, and the following results were obtained. The socio-cultural characterization of the parish of Belisario Quevedo is composed of 60% women and 40% men, the predominant level of education is a secondary school with 39%, and their nationality is 100% Ecuadorian. The economic indicators of the population of Belisario Quevedo are based on income from the primary sector (agriculture and livestock), complemented by income from the commercial sector. The productive sector is based on the cultivation of maize, corn, "chocho," beans, among others, and the presidents of each neighborhood represent the organization of the parish.